2020
DOI: 10.1007/s11657-020-00757-w
|View full text |Cite
|
Sign up to set email alerts
|

Greater maintenance of bone mineral content in male than female athletes and in sprinting and jumping than endurance athletes: a longitudinal study of bone strength in elite masters athletes

Abstract: We investigated longitudinal changes in tibia bone strength in master power (jumping and sprinting) and endurance (distance) athletes of both sexes. Bone mass but not cross-sectional moment of inertia was better maintained in power than endurance athletes over time, particularly in men and independent of changes in performance. Objective Assessment of effects of sex and athletic discipline (lower limb power events, e.g. sprint running and jumping versus endurance running events) on longitudinal changes in bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
(67 reference statements)
4
11
1
Order By: Relevance
“…Longitudinal analysis of bone traits in masters sprint/power athletes has been limited to a single investigation ( 27 ) and no previous data are available on the importance of sustained sport‐specific training on bone changes with aging. In line with our present findings, a recent 4‐year longitudinal study by Ireland and colleagues ( 27 ) found greater maintenance of distal (4%) and mid‐tibial (66%) BMC in masters power (sprinting and jumping) than endurance athletes aged 37 to 85 years. At the distal site, the differences resulted from better maintenance of trabecular BMD, whereas at mid‐tibia, they were explained by the maintenance of cortical thickness and cortical BMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal analysis of bone traits in masters sprint/power athletes has been limited to a single investigation ( 27 ) and no previous data are available on the importance of sustained sport‐specific training on bone changes with aging. In line with our present findings, a recent 4‐year longitudinal study by Ireland and colleagues ( 27 ) found greater maintenance of distal (4%) and mid‐tibial (66%) BMC in masters power (sprinting and jumping) than endurance athletes aged 37 to 85 years. At the distal site, the differences resulted from better maintenance of trabecular BMD, whereas at mid‐tibia, they were explained by the maintenance of cortical thickness and cortical BMD.…”
Section: Discussionmentioning
confidence: 99%
“…At the distal site, the differences resulted from better maintenance of trabecular BMD, whereas at mid‐tibia, they were explained by the maintenance of cortical thickness and cortical BMD. ( 27 ) Longitudinal studies conducted on middle‐aged and older masters long‐distance runners have shown maintained areal BMD at the hip and spine ( 28,29 ) but have not examined changes in bone structure, strength, and volumetric density.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two previous cross-sectional studies based on an anthropometric assessment of lower limb muscle volume [ 35 ] in male 115 track and field masters [ 36 ] and in 54 male master weight lifters [ 37 ] indicated a volume reduction of approximately 6% per age decade. This figure has been confirmed by a recent longitudinal study in 71 track-and-field master athletes with a mean follow-up of 4.2 years that found a reduction in calf muscle cross section, as assessed with computed tomography, by 0.6% per year in men, but no significant change in women [ 38 ]. Moreover, a recent cross-sectional study in 256 track and field masters aged 35–91 years in which whole body skeletal muscle mass was assessed via bio-electrical impedance indicates a reduction by 3.2% and 2.8% per decade in women in men, respectively [ 39 ], which was equalized by a commensurate increase in fat mass.…”
Section: Physiological Changes In Older Athletesmentioning
confidence: 53%
“…As to another question, namely what happens to masters athletes if exercise is continued across the life span, results from cross-sectional studies suggest that the bone benefits attained at young age [ 119 ] persist into old age, although they may fade away with advancing age [ 120 ]. A recent longitudinal study in 71 track and field masters with 4-year follow-up, however, demonstrates that tibia bone mass and strength can be preserved, or even increased in male power athletes, whilst male endurance athletes and female track-and-field masters lose tibia epiphyseal bone mass at a rate of approximately 5% per decade [ 38 ]. It has to be considered, however, that some of the female masters athletes in that study were aged between 50 and 60 years, i.e., within the perimenopausal decade, and that this study could not discern between the effects of aging and of menopause.…”
Section: Physiological Changes In Older Athletesmentioning
confidence: 99%
“…Given that (I) current recommendations suggest that vigorous intensity physical activity (10-13) for young people achieve large health benefits and reduce the risk of developing diseases later in life (11,14,15), including bone health (8,9), (II) HIIT may improve health-related outcomes (19,(21)(22)(23)25,26), and (III) the development of bone health during childhood and adolescence is substantial and may be an important protective factor for osteoporosis and fractures (1), it becomes essential to understand HIIT effects on bone health in adolescents, specially nowadays when this type of exercise is on spotlight. Briefly, recent studies with adults showed that HIIT can be an effective way to improve BMC and BMD (27), and regular powerbased training and competition in sprinting and jumping is associated with better maintenance of bone mass (28).…”
Section: Discussionmentioning
confidence: 99%